2021
DOI: 10.3389/fphys.2021.692361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Venoconstrictive Thigh Cuffs on Dry Immersion-Induced Ophthalmological Changes

Abstract: Neuro-ophthalmological changes named spaceflight associated neuro-ocular syndrome (SANS) reported after spaceflights are important medical issues. Dry immersion (DI), an analog to microgravity, rapidly induces a centralization of body fluids, immobilization, and hypokinesia similar to that observed during spaceflight. The main objectives of the present study were 2-fold: (1) to assess the neuro-ophthalmological impact during 5 days of DI and (2) to determine the effects of venoconstrictive thigh cuffs (VTC), u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…During 3-day DI, Kermorgant et al (2017) showed an increase in ONSD of about 30%, as measured with ultrasound (Pre-DI: 4.64±0.40mm; DI3: 6.01±0.49mm; p <0.001; Kermorgant et al, 2017 ). In DI5-CUFFS, Kermorgant et al (2021) have found a significant increase of ONSD after 5days of DI by 20% in the control group and 14% in the cuffs group ( Kermorgant et al, 2021 ). These ONSD values are equivalent to an elevation of ICP around 20mmHg, the normal range being between 7 and 15mmHg ( Geeraerts et al, 2008 ).…”
Section: Discussionmentioning
confidence: 93%
“…During 3-day DI, Kermorgant et al (2017) showed an increase in ONSD of about 30%, as measured with ultrasound (Pre-DI: 4.64±0.40mm; DI3: 6.01±0.49mm; p <0.001; Kermorgant et al, 2017 ). In DI5-CUFFS, Kermorgant et al (2021) have found a significant increase of ONSD after 5days of DI by 20% in the control group and 14% in the cuffs group ( Kermorgant et al, 2021 ). These ONSD values are equivalent to an elevation of ICP around 20mmHg, the normal range being between 7 and 15mmHg ( Geeraerts et al, 2008 ).…”
Section: Discussionmentioning
confidence: 93%
“…After five days of DI, participants were found to have a loss in muscle strength, muscle fiber atrophy, impaired protein balance, and decreased oxidative capacity, regardless of the use of a thigh cuff. In contrast, measurements on cardiovascular and ophthalmological function carried out by our collaborators have shown a beneficial effect of the thigh cuff to prevent the adverse effects of body fluid redistribution induced by 5 days of DI [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of this study is the low number of subjects in each group ( n = 9). The number of subjects was not specifically powered for bone metabolism criteria, but for change in optic nerve sheath diameter, a primary outcome measure for this protocol (ck Kermorgant et al, 2021 ). This might have been responsible for the lack of significant changes, as seen for example in Glu-OC since statistical difference was achieved with the unique group of 12 subjects in the 1st experiment ( Linossier et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This integrative study was primarily designed to test the efficacy of venoconstrictive thigh cuffs, as countermeasure to limit cephalad fluidshift, on DI-induced deconditioning, in particular for body fluids and related ophthalmological disorders (for results cf. Robin et al, 2020 ; Kermorgant et al, 2021 ). However, several physiological systems interact, including the cardiovascular and musculoskeletal systems.…”
Section: Introductionmentioning
confidence: 99%